Film tourism in Spain: Destination awareness and visit motivation asdeterminants to visit places seen in TV series - Noelia Araújo Vila; José Antonio Fraiz Brea; Pablo De Carlos (European Research on Management and Business Economics (ERMBE), 2021)
TV series have become one of the most successful types of audio-visual product. Their potential to cul-tivate massive loyal audiences makes them an excellent medium for promoting the places they depict,presenting them as attractive destinations, and inducing the phenomenon known as film tourism. Thepresent study aims to shed light on the determinants behind viewers' decisions to visit a destination theyhave seen in a TV series. More specifically, two aspects acknowledged as antecedents of travel decisionswere considered: destination awareness and visit motivation. To this end, quantitative questionnaireswere carried out with domestic tourists during their visits to destinations depicted in Spanish TV series.The collected data was analysed through tests of independence and a binary logistic regression, in whichthe respondents' sociodemographic characteristics were used as control variables. The results corrobo-rate that both factors significantly influence the decision to visit film destinations, whereas the effect ofdestination awareness is stronger.
Keywords: M3; L82; L83; 650; Film tourism; TV series; Destination awareness; Visit motivation; Travel decision